Pengembangan Buku Pengayaan Pada Materi Tembang Dolanan Bagi Siswa Kelas III SD (Piwulang : Jurnal Pendidikan Bahasa Jawa, 2022)
In learning at school, sometimes teachers find it difficult to explain and teach the tembang dolanan due to the lack of teaching materials that explain details about it. The purpose of this study was to determine the teacher's needs for the development of enrichment books, compile a prototype for the development of enrichment books, and describe the results of the expert validation test on the development of enrichment books. This research was conducted using an R&D approach from Borg & Gall. The target sources data are students, teachers, media experts, and material experts. Data collection techniques are interview techniques and filling out questionnaires. The results of this study include (1) the analysis of teacher needs for the development of enrichment books on the material (tembang dolanan), that teachers want interesting complementary teaching materials for learning tembang dolanan for third-grade elementary school students. (2) the development of the prototype includes a book cover designed with children's pictures, while the contents of the book consist of ten lists of dolanan songs and their meanings. (3) The results of the expert validation test got several improvements from the validator, namely, adding page numbers, changing the title font of the dolanan song, correcting wrong diction, correcting wrong lyrics, and replacing some dolanan songs that are not in accordance with learning.